Moocs: viable, unsettling and consistent - Anglada, Lluís (Anuario ThinkEPI, 2014)
The massive online open course (mooc) has had a great impact in the landscape of higher education. Analysts say the MOOCs will have a disruptive effect on universities and teaching practice. Universitieswill be forced to change. The psychopedagogical substrate of the moocs is the "flipped education" model in which learning takes place from discussions with fellow students and teachers. We analyze the impact of moocs in university libraries.
Keywords: Moocs; Higher education; Distance learning; Online learning; Universities; Learning; University libraries.